USE OF ICT IN DISTANCE LEARNING FOR STUDENTS WITH FUNCTIONAL LIMITATIONS - Zaporozhchenko, Ю.Г. (Journal of Information Technologies in Education (ITE), 2014)
The article outlines the main advantages of distance learning (e-learning) for students with functional limitations, describes the types of learning models according to the process of interaction of stakeholders, characterizes the types of ICT applicable to each mode of interaction.